Message fatigue on social media and Covid-19 health behavior intention - Destrity, Nia Ashton; Wardasari, Nilam (Faculty of Communication Sciences Universitas Padjadjaran, 2025)
Continuous health messages regarding Covid-19 are disseminated via social media platforms, covering essential health protocols such as mask-wearing, hand hygiene, physical distancing, crowd avoidance, limited mobility, and social interactions. These messages aim to encourage the adoption of health behaviors among the public. However, the persistent exposure to these messages can lead to message fatigue, potentially causing resistance to health recommendations. Despite numerous studies on message fatigue, none specifically address its occurrence in Covid-19 health messages on social media and its mediation by attitudes toward messages. Moreover, given Indonesia’s collectivist cultural inclination, responses to Covid-19 health messages, may vary. Through an online survey, this study collected quantitative data to explain the level of message fatigue experienced by social media users and the mediating role of attitudes toward messages in contributing to intention in health behaviors related to Covid-19. Meanwhile, qualitative data were used to identify message characteristics that cause and mitigate fatigue for social media users. Findings from 204 respondents reveal that a majority experience moderate levels of message fatigue concerning Covid-19 health messages on social media. Message fatigue plays a role in attitudes toward messages and intentions regarding Covid-19 health behaviors, with attitudes toward messages serving as a mediator between message fatigue and behavioral intention. The study underscores the theoretical and practical implications for addressing message fatigue in health communication campaigns, offering insights into effective strategies for mitigating its impact.